Scratch Music - Cardew, Cornelius 1936-1981 (Cambridge, Massachusetts MIT Press, 1974)
"Any direction modern music will take in England will come about only through Cardew, because of him, by way of him. If the new ideas in music are felt today as a movement in England, it's because he acts as a moral force, a moral centre."This is Morton Feldman's assessment of Cardew's importance, an assessment that took on prophetic status when Cardew cofounded the Scratch Orchestra in 1969. This orchestra was a culmination of the ideals expressed in Cardew's own music in the 1960s when, working in almost total isolation from the musical establishment, he patiently drew together a large group of composers and performers into experimental music through his own compositional activities and through teaching. This group became the nucleus of the orchestra.The draft constitution of the Scratch Orchestra opens as follows: "Definition: A Scratch Orchestra is a large number of enthusiasts pooling their resources (not primarily material resources) and assembling for action (music-making, performance, edification)."Note: The word music and its derivatives are here not understood to refer exclusively to sound and related phenomena (hearing, etc). What they do refer to is flexible and depends entirely on the members of the Scratch Orchestra."The Scratch Orchestra intends to function in the public sphere, and this function will be expressed in the form offor lack of a better wordconcerts."This lively book on the repertory the orchestra created is as much graphic and visual as it is verbal and about aural events and happenings. This is because scratch composers are often possessed of strong visual imaginationsafter all, scratch music itself (as the above "Note" suggests) is meant to be perceived by the eye and indeed by all the senses and not just by the ear (the sensual mix varies from one composition to another). Also, the notation used in preparing scores for actual performance may be graphic, collage, verbal, musical, or whatnot.The main body of the book depicts a selection of such scores. They are composed of written words, photographs, maps, graphs, diagrams, musical flow charts, conventional musical notation, whimsical drawings, playing cards, crossword puzzles, and various other things. Together, they give the reader some idea of what it is like to put on a scratch music event.
Keywords: Composing